From boundary waters to watersheds: Legal change and the geography of the Great Lakes‐St. Lawrence system. (4th November 2016) - Benidickson, Jamie
Abstract : It is appropriate to recognize an evolving legal and institutional perspective on the Great Lakes‐St. Lawrence system (GL‐SL) as a means of furthering the understanding that is provided from established cartographic, bio‐geological, historic, and cultural perspectives. This paper describes elements of that evolution from a one‐dimensional legal conceptualization of the GL‐SL as a boundary reflecting sovereign autonomy and state security, through a more complex recognition of the water system involving navigation, fisheries, and water supply, to a more comprehensive acknowledgment of basin‐ and ecosystem‐oriented approaches where land‐use activities and influences ranging from groundwater flows through air‐borne contamination must be accounted for. The Boundary Waters Treaty of1909 and the Great Lakes Water Quality Agreement (1972–2012) provide general points of reference. Des eaux limitrophes aux bassins versants : le changement juridique et la géographie du système des Grands Lacs et du Saint‐Laurent: Il est opportun de se situer dans une perspective évolutive en matière juridique et institutionnelle afin de faire avancer les connaissances sur le système des Grands Lacs et du Saint‐Laurent (GL‐SL) issues des perspectives cartographique, biogéologique, historique et culturelle. Cet article brosse un tableau de cette évolution, d'abord par une conceptualisation juridique des GL‐SL qui se limite à une zone limitrophe témoignant de l'autonomie souveraine et la sécurité de l'État ; puis par une vision plus complexe du système hydrographique qui associe la navigation, les pêches et l'approvisionnement en eau ; et finalement par une vision globale des approches axées sur le bassin et l'écosystème qui tient compte de l'ensemble des activités et des influences liées à l'usage des terres, allant de l'écoulement des eaux souterraines à la contamination atmosphérique. Le Traité des eaux limitrophes de 1909 et l'Accord relatif à la qualité de l'eau dans les Grands Lacs (1972‐2012) apportent quelques points de repère généraux. Key Messages: The legal framework applicable to the geography of the Great Lakes‐St. Lawrence has evolved. At the time of the Boundary Waters Treaty a linear, boundary‐oriented perspective prevailed. Following the Great Lakes Water Quality Agreement of 1972, the introduction of basin‐ and ecosystem‐oriented approaches altered the legal framework for the Great Lakes‐St. Lawrence system.